The unbeatable Squirrel Girl. Volume 6, Who run the world? Squirrels - North, Ryan 1980- (Marvel Worldwide, Inc., 2017)
It's a normal, quiet day at Empire State University, filled with lots of lectures and higher education and students learning quietly. But don't turn away, there's also going to be a fist fight! A big one! And Doreen Green will also get a new Flying Squirrel suit from a mystery benefactor that would render her even more unbeatable, if such a thing were scientifically possible! That pretty much means crime is over forever. There definitely can't be a new super villain in town conspiring to mold Squirrel Girl into the perfect minion ... or is there?! Gasp at a secret invasion of character motivations! Thrill at a civil war of emotions! Boggle as monsters truly get unleashed and Doreen's fate hangs in the balance! Also, machine-gun-wielding bears! It's squirrels and girls and punching, oh my!